The role of pituitary growth hormone in the regulation of albumin synthesis and catabolism - Kernoff, Leslie Maurice (Department of Medicine, 2020)
Some three years ago I availed myself of an opportunity of pursuing a research project in the Department of Medicine at this Medical School. At that time, a long established interest in the study of plasma albumin metabolism was given fresh impetus by the development of techniques which overcame the problem of measuring rates of albumin synthesis and catabolism under conditions of metabolic chonge. Interest in the Department had centred mainly upon the nature of the adaptive changes occurring in albumin metabolism in response to altered dietary protein intake, and by the time I was due to take up my appointment many of these adaptive changes had been clearly defined. The factors mediating these changes however remained unknown.